New species of Traumatomutilla André in the T. tabapua and T. integella species-groups (Hymenoptera, Mutillidae) - Bartholomay, Pedro R.; Williams, Kevin A.; Luz, David R.; Oliveira, Marcio L. (Zootaxa, 2018)
Five new species of Traumatomutilla André from Brazil are described: T. fratres Bartholomay & Williams sp. nov., T. anhanga Bartholomay & Williams sp. nov., T. barathra Bartholomay & Williams sp. nov., T. poranga Bartholomay & Williams sp. nov. and T. pantherina Bartholomay & Williams sp. nov. Traumatomutilla tabapua Casal, 1969, T. luscoides André, 1908 and T. integella (Cresson, 1902) are redescribed. T. verecunda (Cresson, 1902) is proposed as junior synonym of T. integella based on morphological evidence. T. luscoides is transferred from the T. integella to the T. tabapua species-group.